FAMILY CARE EDUCATION IN INDONESIA - Rochyanto, Hendy Agus (IJRDO- Journal of Educational Research, 2017)
Indonesia is a developing country with a high population. According to the census resultpublication in august 2010 that mentioned the population in Indonesia is 237,556,363 people.Those are consisting of man is 119,507,600 and women is 118,048,783 people, with growthrate is 1,49 percent per year. According of the law number 10 of 1992, the family planningprogram is an effort to increase awareness and participation of the community through of thematuration of marriage age, birth control, family resilience, birth control, family resiliencedevelopment, improvement of small family welfare, happy and prosperous Family Planningprograms is an integral part of the national development program and aims to createeconomic, spiritual and socio-cultural welfare of the Indonesian population in order toachieve a good balance with national production capability. Family planning is an attempt tomeasure the number and distance of the desired child. In order to achieve this, then madeseveral ways or alternatives to prevent or delay pregnancy.Family Planning goals isImproving the wlfare of people and welfare of controling the emerging and controling of thegrowth of Indonesian population, and create of a quality population human resources andincrease family welfare.